HISTÓRIA EM QUADRINHOS: A DIDATIZAÇÃO DE UM GÊNERO GRÁFICO-VISUAL - MACAGNAN, MARIA J. P.; SANTOS, ROSITA D. S.; MACAGNAN, MARIA J. P.; SANTOS, ROSITA D. S.; MACAGNAN, MARIA J. P.; SANTOS, ROSITA D. S. (Salão do Conhecimento, 2013)
Resumo